2000
DOI: 10.1115/1.1318205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NO Models on the Prediction of NO Formation in a Regenerative Furnace

Abstract: A study of the effects of nitric oxide (NO) models on the prediction of NO formation in a gas-fired regenerative furnace with highly preheated air was undertaken. Three chemical kinetic processes for NO formation/depletion, i.e., thermal NO, prompt NO, and NO reburning, are included. In the thermal NO model, the sensitivity encountered when using two different approaches, namely the equilibrium approach and the partial equilibrium approach, for determining the O radical concentration was studied. The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…(2) The rate of the reaction for NO x is slower than that of the combustion reaction. Thus, the NO x mechanism can be decoupled from the main combustion mechanism [47]. (3) NO x chemistry displays a negligible influence on the predicted flow field, temperature, and major combustion product concentrations [48].…”
Section: No X Modelmentioning
confidence: 99%
“…(2) The rate of the reaction for NO x is slower than that of the combustion reaction. Thus, the NO x mechanism can be decoupled from the main combustion mechanism [47]. (3) NO x chemistry displays a negligible influence on the predicted flow field, temperature, and major combustion product concentrations [48].…”
Section: No X Modelmentioning
confidence: 99%
“…Some researchers have studied NO x emissions from other industrial furnaces. Ishii et al [17] have built a numerical model to investigate the NO x emissions in a regenerative furnace, in this model three chemical kinetic processes for NO x formation are included. Khalilarya and Lotfiani [18] have provided a numerical study of flow pattern and its effect on NO x emissions in a single chamber square tangentially fired furnace.…”
Section: Introductionmentioning
confidence: 99%
“…Ishii et al [1,2] showed that 1579 K of preheat inlet air temperature can be obtained in a regenerative furnace. Meanwhile, it produced low NO x emissions and over 70% heating efficiency.…”
Section: Introductionmentioning
confidence: 99%